THE EFFECTIVENESS OF THE JIN'S 3 NEEDLE THREAD LIFT METHOD AND WATERMELON JUICE ON OBESITY IN MEDIKA AKUPUNKTUR BOJONEGORO - Resti Anggraini Milana; Maria Dewi Christiyawati; Sholichan Badri (HAKTI : Indonesian Acupuncture Therapists Association, 2023)
Background: Obesity is an excessive accumulation of fat that can interfere with health. During this pandemic, a lot of food, sweet drinks, and the lack of activities we work from home are also one of the causes of obesity. Based on Riskesdas data, the population's consumption of vegetables and fruit is still low. Objective: To determine the effectiveness of the Jin's 3 needle thread lift method and watermelon juice on obesity in Acupuncture Medicine. Methods: With experimental two group pretest - posttest control design, analysis using Wilcoxon test with 30 samples, for 2 weeks. The dependent variable is body weight, (BMI), waist circumference, upper arm circumference (LILA), visceral fat. The independent variables are the Jin's 3 needle thread lift Method and Watermelon Juice. Time and place: January - March 2021, at Medika Acupuncture, Jl. Ahmad Dahlan No. 22 Bojonegoro Regency, East Java. Results: The average reduction in obesity in the threadlift jin's 3 needle group was 1.55 kg, waist circumference was 4.77cm, upper arm circumference was 4.93%. visceral fat 0.86, BMI is 0.6 kg/m2. In the jin's 3 needle thread lift group and watermelon juice, the body weight was 2.6 kg, waist circumference is 6.2 cm, upper arm circumference is 8.3%, visceral fat is 1.7. BMI is 1.1 kg/m2. Wilcoxon test results get 0.001, 0.001, 0.001, 0.001, 0.001 < 0.05. Conclusion: The jin's 3 needle thread lift method and watermelon juice can be said to be significant and effective against obesity at Medika Acupuncture, Bojonegoro.